A critical review of camping research and direction for future studies. (October 2014) - Brooker, Ed; Joppe, Marion
Camping is a popular form of accommodation and outdoor recreation, providing liminal opportunities to escape, rejuvenate, and socialize with family, friends, and fellow campers. Surprisingly, limited academic research has been conducted on the business and market segments of campgrounds. In order to, at least partly, address this identified gap, a literature review was undertaken of the articles published on campgrounds and caravan parks in the past 50 years, the majority of which have originated in either the United States or Australia. This article presents the results of this investigation, the aim of which was to (1) identify and classify research on US campgrounds and Australian caravan parks, (2) describe the main trends revealed, and (3) present a future research agenda.